2009
DOI: 10.1103/physrevb.80.060101
|View full text |Cite
|
Sign up to set email alerts
|

Role of di-interstitial clusters in oxygen transport inUO2+xfrom first principles

Abstract: Using density functional theory, we examine a recently discovered structure for di-interstitial oxygen clusters in UO 2+x in which three oxygen ions share one lattice site. This di-interstitial cluster exhibits a fast diffusion pathway; the migration barrier for these clusters is approximately half of that for mono-interstitials. Using kinetic Monte Carlo, we calculate the diffusivity of oxygen with and without the di-interstitial mechanism as a function of x and find that oxygen transport is significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 41 publications
9
72
1
Order By: Relevance
“…OFT tends to agree with OFT +U in reproducing trends, but the quantitative details differ 6 [16]. Similarly here, the difference in energy between the two phases might change if calculated with DFT+V.…”
mentioning
confidence: 77%
“…OFT tends to agree with OFT +U in reproducing trends, but the quantitative details differ 6 [16]. Similarly here, the difference in energy between the two phases might change if calculated with DFT+V.…”
mentioning
confidence: 77%
“…In order to simplify the calculation of defect properties the latter two contributions are ignored in the present study. Recent reports have shown that the LDA/GGA+U methodology correctly describes many of the relevant properties of UO 2 and UO 2+x 42,[44][45][46][47][48][49][50][51][52][53][54][55][56] . In accordance with earlier LDA+U studies the U and J values were set to U = 4.5 eV and J = 0.51 eV 46 .…”
Section: Approachmentioning
confidence: 99%
“…The effects of chemical environment on the ground states and excitation spectra of f -electrons are particularly interesting, since they are responsible for splitting the otherwise 2J + 1-fold degenerate free-ion ground state 2S+1 L J , giving rise to rich physics and applications. Recently, actinide dioxides in the cubic fluorite structure have attracted renewed theoretical interest in the context of their use as nuclear fuels [1][2][3][4][5][6][7][8][9][10] . The crystal field (CF) method is a well established tool for describing the ligand environment of localized electrons.…”
Section: Introductionmentioning
confidence: 99%